Lenguaje, medios de comunicación y realidad sociojurídica: La influencia de los medios de comunicación en valoración de la primera etapa del proceso de paz en Colombia (2011-2013) - Flórez Muñoz, Daniel E. (Archivos de criminología, seguridad privada y criminalística, 2022)
The main objective of this paper is to analyze the development of the Peace Dialogues in Colombia, which is intended to deduce that the construction of peace has been carried out in our country in a purely discursive manner. For this, we are dedicated to studying the way in which discourse allows man to both modify social reality and create completely different realities, as well as the influence that discourse analysis has on the political field regarding the conceptualization of power.